Physical and mechanical properties of composite boards based on wood fiber/palm kernel shell with different polyurethane composition - Zamri, F. A.; Primus, Walter Charles; Abdullah, Nur Ashikin Psyquay; James Gerusu, Geoffery (Faculty of Engineering, Universiti Putra Malaysia, 2016)
The oil palm industry has brought significant impacts to the economy, social, geographical as well as the environment. The decrement of wood resources and the concern of waste produced from palm oil production has become one of the major reasons in development of fiberboard products. A series of fiberboard samples have been fabricated and the effect of polyurethane adhesive (30, 40 and 50 %) into filler: wood fiber/oil palm kernel shell at ratio of 75/25 has been studied in terms of physical and mechanical properties. The results showed that flexural modulus, flexural strength, tensile modulus, and hardness were increased with the increase of polyurethane adhesive percentage. The effects were also explained in terms of porosity and surface morphology. The board met the JIS A 5905 for 5-type and can be classified as medium density fibreboard.